2009
DOI: 10.1002/adma.200900238
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Transformations on Solid Substrates: Efficient Avenues to Surface Modification

Abstract: The performance of solid substrates is not only governed by their molecular constitution, but is also critically influenced by their surface constitution at the solid/gas or solid/liquid interface. In here, we critically review the use of orthogonal chemical transformations (so‐called click chemistry) to achieve efficient surface modifications of materials ranging from gold and silica nanoparticles, polymeric films, and microspheres to fullerenes as well as carbon nanotubes. In addition, the functionalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
104
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 205 publications
0
104
0
Order By: Relevance
“…Click-type reactions are employed for a range of purposes, including surface modification [6] and the generation of complex macromolecular architectures [5] . Quantitative orthogonal conjugation becomes especially attractive where polymeric building blocks are joined to yield block copolymers, [7][8][9][10][11] which are not obtainable by alternative means (i.e., sequential chain extension via living/controlled (radical) polymerization).…”
Section: Introductionmentioning
confidence: 99%
“…Click-type reactions are employed for a range of purposes, including surface modification [6] and the generation of complex macromolecular architectures [5] . Quantitative orthogonal conjugation becomes especially attractive where polymeric building blocks are joined to yield block copolymers, [7][8][9][10][11] which are not obtainable by alternative means (i.e., sequential chain extension via living/controlled (radical) polymerization).…”
Section: Introductionmentioning
confidence: 99%
“…Compound 2c was isolated by column chromatography (cyclohexanes/EtOAc, 9:1) as a solid foam (71 mg, 45 %). 1 …”
Section: Ethoxy Tri(2ј5ј-dimethyl-4јј-iodo[41ј;4ј1јј]terphenyl)silmentioning
confidence: 97%
“…68-70°C. 1 1, 8 mL). This mixture was degassed with argon purge for 5 min, and the reaction was initiated by the addition of 6 (0.10 g, 0.15 mmol) and placed in an oil bath at 70°C for 12 h. The catalyst was filtered off and washed with acetonitrile (50 mL).…”
Section: Ethoxy Tri(2ј5ј4јј-trimethoxy[41ј;4ј1јј]terphenyl)silanementioning
confidence: 98%
See 1 more Smart Citation
“…Grafting from or rather onto surfaces isespecially since the advent of living/ controlled radical processes -a popular route to place low polydispersity polymers with variable characteristics onto surfaces. A recent review of surface modification via click chemistry approaches [20] has demonstrated that several types of surface have by now been modified via click chemistry. Again, we question whether this flurry of activity is merely an expression of scientific 'me-tooism' or whether a deeper conceptual driving force is at work that is based on the efficiency and modularity of the click chemistry concept.…”
Section: Introductionmentioning
confidence: 99%